2019
DOI: 10.1177/1461444818823546
|View full text |Cite
|
Sign up to set email alerts
|

Individual pastime or focused social interaction: Gendered gaming practices among Danish youth

Abstract: This article outlines how gaming and video gameplay among Danish youth can be integral parts of everyday practices. The article is based on a mixed-methods study of video gameplay patterns among Danish children and young people aged 10–18 years. The study included a survey with a stratified random sample ( N = 1560), follow-up in-depth interviews using purposive sampling from the survey respondents ( N = 19) and focus group interviews with boys and girls ( N = 2). We argue that pronounced differences in boys’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
3
4
0
Order By: Relevance
“…In relation to the gender differences between gamers, the sample complies with Crawford (2011) and Thornham's (2008) thoughts, who conceive of gaming as a predominantly male practice with a tendency towards a stereotypical binary representation of gender. The composition of the sample is also consistent with Thorhauge and Gregersen (2019), who find gendered gaming practices, with females using gaming to relax and males preferring competition and action.…”
Section: Method Data and Ethicssupporting
confidence: 76%
See 2 more Smart Citations
“…In relation to the gender differences between gamers, the sample complies with Crawford (2011) and Thornham's (2008) thoughts, who conceive of gaming as a predominantly male practice with a tendency towards a stereotypical binary representation of gender. The composition of the sample is also consistent with Thorhauge and Gregersen (2019), who find gendered gaming practices, with females using gaming to relax and males preferring competition and action.…”
Section: Method Data and Ethicssupporting
confidence: 76%
“…Gaming is an everyday practice that shapes young people's identities and-when linked to other everyday practices (like sports and education)-enables dynamic social interactions (Pargman & Jakobsson, 2008;Thorhauge & Gregersen, 2019).…”
Section: Background: Young People's Online Practices and The Covid-19 Lockdown In Denmarkmentioning
confidence: 99%
See 1 more Smart Citation
“…A representative study of gamer habits amongst Danish children found that a majority of boys prefer competitive multi-player gaming, whereas a majority of girls use games as an individual pastime as a break or for 'zooming out' -e.g. from intense communication on social media (Thorhauge & Gregersen, 2019). Similar differences amongst boys and girls' gamer habits can be found in the other Nordic countries (e.g.…”
Section: Introductionsupporting
confidence: 63%
“…Yet, we did not find significant gender differences in physical activity habits or importance, although boys were significantly more active sports video game players. Such findings may lead to promising future hypotheses whereby involvement in team sports such as floorball, ice hockey, and football -that have, in Finland, traditionally been more popular among boys than girls (Mononen et al, 2016) -invite the participants of their social worlds to also play parallel video game simulations (NBA, NHL, FIFA) or virtual reality experiences (Maloney, 2021) As reported by Thorhauge and Gregersen (2019), gender may also explain why video games are engaged differently in the first place, as "boys use [video] gaming to gear into a social domain of cooperative team play where social connections with male peers are established .... in contrast, most girls seem to use gaming to get away from the otherwise intensely social lives" (p. 1460). These gender differences can be further magnified by male-dominated video game representations (Ivory, 2006).…”
Section: Discussionmentioning
confidence: 98%